The most effective natural cures on Earth : the surprising, unbiased truth about what treatments work and why - Bowden, Jonny (Fair Winds Press, 2011)
Take back your health naturally-- without the drugs, side effects, and hassle! Bowden tells you which foods, vitamins, minerals, herbs, amino acids, and natural treatments will treat your conditions.